The Effects of the Students’ Hierarchy of Needs in an Indonesian Private Academy on the Intention to Buy in Social Commerce - Fatimah Muthmainnah; Fergyanto E. Gunawan (CommIT (Communication and Information Technology) Journal, 2020)
In line with Internet users’ growth in Indonesia, many people buy and sell goods and services through social networking sites. This activity is social commerce, and it primarily affects the millennials, such as private academy students. The research is conducted to determine the effects of the hierarchy of needs in a private academy in Indonesia on students’ intentions to buy in social commerce. Facebook, Instagram, and Whatsapp are the used social commerce in the research. The questionnaire is answered by 126 respondents consisting of indicators from Maslow’s hierarchical needs. The analysis technique is Partial Least Square (PLS) with the SmartPLS 3.0 program. Hypothesis test results show that transcendence, self-actualization, cognitive needs, and physiological needs have no significant effect on the intention to buy in social commerce. Meanwhile, esteem needs, safety needs, aesthetic needs, and belonging and love needs affect intention to buy.